Effects of Hydration on the Mechanical Properties of Salt-Doped Poly(methyl methacrylate) - Asae Ito; Naoki Uchida; Yusuke Hiejima; Koh-hei Nitta (Molecules, 2025)
The mechanical performance of poly(methyl methacrylate) (PMMA) is highly sensitive to moisture absorption, which induces plasticization and softening. In this study, we investigated the ductilization mechanism of PMMA by incorporating various metal salts with different cations (Li+ and Mg2+) and controlling water absorption through hygroscopic interactions. A nonequilibrium constitutive model is introduced, in which localized water domains around salt-rich regions gradually diffuse into the PMMA matrix during tensile deformation. The stress–strain behavior is described by combining rigid (dry) and soft (hydrated) matrix components, connected through an internal kinetic variable governed by the strain-dependent diffusion rate. The model successfully reproduces experimental tensile data and captures the transition from brittle to ductile behavior as a function of the moisture content. Notably, Mg salts exhibit stronger water binding and slower moisture redistribution than Li salts, resulting in distinct mechanical responses. These findings provide a mechanistic framework for tailoring the ductility of hygroscopic polymer systems via ion–water–polymer interactions.